Upaya Menggunakan Whatsapp Bisnis Dalam Branding Dan Pengembangan UMKM Oleh Mahasiswa KKNT MBKM UPN “Veteran” Jawa Timur - Zumrotul Fitriyah; Natasya Intan Ayu Praditha; Hanif Ardhi Pranata; Galuh Kinanti (Politeknik Kampar, 2023)
As long as there is an internet connection, social media can be accessed by anyone, regardless of location or time zone. Small and medium entrepreneurs use social media that is widely accessible, simple, and fast as a marketing medium to be bolder in promoting their products. The material in the UPN